Hemochromatosis in a β‐thalassemia minor patient with H63D homozygous mutation: A case report. Issue 12 (12th July 2020) - Pokhrel, Nishan Babu; Khanal, Shambhu; Chapagain, Parikshit; Pokhrel, Biraj; Shrestha, Anjan
Abstract: β‐thalassemia heterozygosity can cause significant iron overload when accompanied by HFE gene mutations and inappropriate iron supplementation. Abstract : β‐thalassemia heterozygosity can cause significant iron overload when accompanied by HFE gene mutations and inappropriate iron supplementation.